HAL – HAL POKOK DALAM PEMBUATAN SUATU KONTRAK - Niru Anita Sinaga; Nunuk Sulisrudatin (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2017)
Today the business is growing, whether small, middle and top. Talking about the business can not be separated from what is called a contract. Almost every day we do a contract. It is therefore necessary understanding of matters relating to a contact, such as: What is a contract, the terms of validity of the contract, the principles of the contract, the object of the contract, the contract period, the contract form, the parties involved, the rights and obligations of the parties, the structure and anatomy of contracting, dispute settlement and expiration of the contract. The purpose of making the same contract with the purpose of the law in general, namely the creation of justice, order and legal certainty. However, in practice often led to problems. To overcome this, hence in making contracts or agreements let first understand about the contract, the consequences and the conditions to be met in the manufacture of the contract. Keywords: Contract and subject matter.